The impact of macroprudential housing finance tools in Canada: 2005 - 10 - Jason Allen; Timothy Grieder; Brian Peterson; Tom Roberts (Bank of Canada, 2016)
This paper combines loan-level administrative data with household-level survey data to analyze the impact of recent macroprudential policy changes in Canada using a microsimulation model of mortgage demand of first-time homebuyers. Policies targeting the loan-to-value ratio are found to have a larger impact than policies targeting the debtservice ratio, such as amortization. This is because there are more wealth-constrained borrowers than income-constrained borrowers entering the housing market.
Keywords: D14; G28; C63; 330; Financial system regulation and policies